Parent-son decision-making about human papillomavirus vaccination: a qualitative analysis - Alexander Andreia B; Stupiansky Nathan W; Ott Mary A; Herbenick Debby; Reece Michael; Zimet Gregory D (BMC, 2012)
Abstract Background Licensed for use in males in 2009, Human Papillomavirus (HPV) vaccination rates in adolescent males are extremely low. Literature on HPV vaccination focuses on females, adult males, or parents of adolescent males, without including adolescent males or the dynamics of the parent-son interaction that may influence vaccine decision-making. The purpose of this paper is to examine the decision-making process of parent-son dyads when deciding whether or not to get vaccinated against HPV. Methods Twenty-one adolescent males (ages 13-17), with no previous HPV vaccination, and their parents/guardians were recruited from adolescent primary care clinics serving low to middle income families in a large Midwestern city. Dyad members participated in separate semi-structured interviews assessing the relative role of the parent and son in the decision regarding HPV vaccination. Interviews were recorded, transcribed, and coded using inductive content analysis. Results Parents and sons focused on protection as a reason for vaccination; parents felt a need to protect their child, while sons wanted to protect their own health. Parents and sons commonly misinterpreted the information about the vaccine. Sons were concerned about an injection in the penis, while some parents and sons thought the vaccine would protect them against other sexually transmitted infections including Herpes, Gonorrhea, and HIV. Parents and sons recalled that the vaccine prevented genital warts rather than cancer. The vaccine decision-making process was rapid and dynamic, including an initial reaction to the recommendation for HPV vaccine, discussion between parent and son, and the final vaccine decision. Provider input was weighed in instances of initial disagreement. Many boys felt that this was the first health care decision that they had been involved in. Dyads which reported shared decision-making were more likely to openly communicate about sexual issues than those that agreed the son made the decision. Conclusion Parents and sons play an active role in the decision-making process, with an individual's role being influenced by many factors. The results of this study may be used to guide the messages presented by clinicians when recommending the HPV vaccine, and future vaccine uptake interventions.